2017
DOI: 10.1016/j.ceramint.2017.02.118
|View full text |Cite
|
Sign up to set email alerts
|

Deep-red emission of Mn4+ and Cr3+ in (Li1−xAx)2MgTiO4 (A=Na and K) phosphor: Potential application as W-LED and compact spectrometer

Abstract: Mn 4+ doped and Mn 4+ /Cr 3+ co-doped alkali metal titanate phosphors have been prepared by solid state reaction method. A part of Li + ions in the Li 2 MgTiO 4 : Mn 4+ are substituted with Na + and K + ions and consequently the intensity of Mn 4+ emission at 678 nm is enhanced by 1.7 and 2.5 times, respectively. In the Mn 4+ /Cr 3+ co-doped (Li 0.95 K 0.05) 2 MgTi 0.999 O 4 , both emission of Cr 3+ at 726 nm and emission of Mn 4+ at 678 nm of Mn 4+ are observed. It is interesting to find that the intensity ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Indeed, no narrow bands or fine spectral features are observed in the emission spectra of Na 4 Mg 1−2x Mn x (WO 4 ) 3 phosphors even at 78 K. In addition, metal−oxygen bond distances for the Na0/Mg/Mn site are significantly longer than those reported for the few Mn 4+ -activated phosphors for which asymmetric and broadened vibronic emission from the 2 E state is observed (type B phosphors in the classification proposed by Adachi 25 ); these are Li 2 Mg 2 Ti 3 O 8 (1.90−2.02 Å) 26 and Li 2 MgTiO 4 (2.08 Å). 27 Longer metal−oxygen distances lead to a weaker crystal field and, 28 ultimately, to broadband red emission from Mn 4+ . 29−32 Emission intensities increase up to x = 0.030 and then decrease due to concentration quenching (see inset of Figure 5a).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Indeed, no narrow bands or fine spectral features are observed in the emission spectra of Na 4 Mg 1−2x Mn x (WO 4 ) 3 phosphors even at 78 K. In addition, metal−oxygen bond distances for the Na0/Mg/Mn site are significantly longer than those reported for the few Mn 4+ -activated phosphors for which asymmetric and broadened vibronic emission from the 2 E state is observed (type B phosphors in the classification proposed by Adachi 25 ); these are Li 2 Mg 2 Ti 3 O 8 (1.90−2.02 Å) 26 and Li 2 MgTiO 4 (2.08 Å). 27 Longer metal−oxygen distances lead to a weaker crystal field and, 28 ultimately, to broadband red emission from Mn 4+ . 29−32 Emission intensities increase up to x = 0.030 and then decrease due to concentration quenching (see inset of Figure 5a).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Almost all the PL studies on type O-B phosphors were performed from room temperature up to 500 K, but not at any temperatures lower than room temperature. [107][108][109][110] These studies reported no clear change in the PL spectral feature from room temperature to 500 K and, as a result, did not enable to explicitly determine the ZPL emission energies in such phosphors. Only a study by Jin et al 31 performed PL measurements from T = 77 to 500 K. However, any fine structure characterizing the ZPL emission transition of type O-B phosphor was not observed in the PL spectra even at 77 K. Therefore, we estimate the ZPL emission energies 2 E g for type O-B phosphors by analyzing the room-temperature PL spectra and assuming a Poisson distribution function of Eq.…”
Section: Systemmentioning
confidence: 96%
“…In the range of 320-400 nm and 490-530 nm, R increases with the excitation wavelength increasing, while R decreases as the excitation wavelength increase in the range of 400-480 nm. Due to the unique properties, the BMA: Mn 4+ , Cr 3+ samples can be used in wavelength detection in a certain wavelength range because the excitation wavelength might be obtained by calculating the emission intensities of Mn 4+ and Cr 3+ to obtain the integrated intensity ratio R. 33 Absolute sensitivity S a for the wavelength detection is calculated by Eq. 8: Relative sensitivity S r is expressed by Eq.…”
Section: R I I 7 Cr Mnmentioning
confidence: 99%